Desentralisasi Asimetris, Alternatif Bagi Masa Depan Pembagian Kewenangan di Indonesia - Nur Ika Fatmawati (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Decentralization, both asymmetrical and symmetrical, in Indonesia will continue to be a serious concern for the study of politics and government. Indonesia has distinctive characteristics that make a study of the pattern of relations between the center and the regions always trying to find a more ideal format. The third characteristic is geographical distribution, demographic distribution and economic distribution centered on Java (economics even based in Jakarta). The agreement made by Indonesia in the form of a unit made the pull relationship between the center and the regions filled with political and economic considerations. The granting of special autonomy to Aceh and Papua, which accompanies long separation from Indonesia shows the complexity of the problems of relations between the center and the regions.